2018
DOI: 10.18512/1980-6477/rbms.v17n1p135-146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Expected Gain in Three Maize Populations

Abstract: - The study of genetic variability in populations undergoing recurrent selection is important to quantify their real potential for breeding purposes. In the present work, three semiexotic maize populations were evaluated on their yield potential and variability for continuing the recurrent selection program. Half-sib families representing three semiexotic populations CRE-01, CRE-02, CRE-03 were evaluated for yield and agronomic traits male flowering (MF), plant height (PH), ear height (EH), ear placement (EP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…when compared with data presented by Candido and Andrade (2008), Andrade and Miranda Filho (2008), Hallauer et al (2010) and Faluba et al (2010) and similar to estimates by Souza et al (2018). For GY, the estimate of 588.1 (g pl -1 ) 2 (hightech environment) was superior to the mean found by Hallauer et al (2010) and Reis et al (2014), similar to estimates by Souza et al (2018) for the populations CRE-1 and CRE-2, but lower than the estimate found by Faluba et al (2010) for UFV 7 population (622.7 (g pl -1 ) 2 ). For TB, the additive variances were 21.9 (high-tech) and 34.7 (branches pl -1 ) 2 (lowtech), close to that obtained by Souza Júnior et al (1985) (28.55), Souza et al (2018) (19.29 and 18.9) and higher than that obtained by Andrade and Miranda Filho (2008) (13.57 (branches pl -1 ) 2 ).…”
Section: Jac Andradesupporting
confidence: 89%
See 4 more Smart Citations
“…when compared with data presented by Candido and Andrade (2008), Andrade and Miranda Filho (2008), Hallauer et al (2010) and Faluba et al (2010) and similar to estimates by Souza et al (2018). For GY, the estimate of 588.1 (g pl -1 ) 2 (hightech environment) was superior to the mean found by Hallauer et al (2010) and Reis et al (2014), similar to estimates by Souza et al (2018) for the populations CRE-1 and CRE-2, but lower than the estimate found by Faluba et al (2010) for UFV 7 population (622.7 (g pl -1 ) 2 ). For TB, the additive variances were 21.9 (high-tech) and 34.7 (branches pl -1 ) 2 (lowtech), close to that obtained by Souza Júnior et al (1985) (28.55), Souza et al (2018) (19.29 and 18.9) and higher than that obtained by Andrade and Miranda Filho (2008) (13.57 (branches pl -1 ) 2 ).…”
Section: Jac Andradesupporting
confidence: 89%
“…For GY, heritability at mean level (56% in high-tech and 41.7% in low-tech) was 3.8 and 4.9 times higher than at plant level. Heritability of these magnitudes was also found by Andrade and Miranda Filho (2008), Candido and Andrade (2008), Faluba et al (2010) and Souza et al (2018). Araújo et al (2005) also obtained similar estimate for the population CMS 39, evaluated at 0.9 m spacing (44.6%), and lower estimates at 0.5 m spacing (29.5%).…”
Section: Jac Andradesupporting
confidence: 67%
See 3 more Smart Citations